Role of Exosomes in Immune Microenvironment of Hepatocellular Carcinoma. (28th January 2022) - Chen, Xiaojing; Chi, Hao; Zhao, Xiaozhao; Pan, Rui; Wei, Ying; Han, Yunwei
Abstract : Hepatocellular carcinoma (HCC) is the most common primary liver cancer. Since most patients with HCC are diagnosed at the intermediate or advanced stage and because HCC has a high incidence of metastasis and recurrence, it is one of the leading causes of cancer death. Exosomes are a subtype of extracellular vesicles and are typically 30–150 nm in diameter. Originating from endosomes, they can be secreted by almost all living cells. They are widely present in various body fluids and serve as an important medium for the interactions between cells. A series of studies have revealed that exosomes-mediated intercellular transfer of proteins, nucleic acids, and metabolites plays a crucial role in the initiation and progression of HCC, hypoxia and angiogenesis, chemotherapy sensitivity, and cell death mode and regulates the immune microenvironment. In this paper, we reviewed the recent researches on the multiple roles of tumor-associated exosomes in the progression of HCC. We laid particular focus on those researches that reveal how exosomes regulate the tumor immune microenvironment (TIME) and how exosomal cargos affect the progression of HCC. Besides, we emphasize some prospective directions to achieve a more accurate and complete analysis of the HCC immune microenvironment.